2022
DOI: 10.3390/cells11213476
|View full text |Cite
|
Sign up to set email alerts
|

Stem-Cell-Based Therapy: The Celestial Weapon against Neurological Disorders

Abstract: Stem cells are a versatile source for cell therapy. Their use is particularly significant for the treatment of neurological disorders for which no definitive conventional medical treatment is available. Neurological disorders are of diverse etiology and pathogenesis. Alzheimer’s disease (AD) is caused by abnormal protein deposits, leading to progressive dementia. Parkinson’s disease (PD) is due to the specific degeneration of the dopaminergic neurons causing motor and sensory impairment. Huntington’s disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 264 publications
(293 reference statements)
0
7
0
2
Order By: Relevance
“…Stem cell transplants are being studied for therapeutic use for several conditions. 6 Prior work in mice shows that transplant of GABAergic progenitors in the dentate gyrus of the hippocampus reduces seizures in the Pilo-TLE model. 7 How exactly this happens is not well-understood.…”
Section: Epilepsy Currentsmentioning
confidence: 99%
“…Stem cell transplants are being studied for therapeutic use for several conditions. 6 Prior work in mice shows that transplant of GABAergic progenitors in the dentate gyrus of the hippocampus reduces seizures in the Pilo-TLE model. 7 How exactly this happens is not well-understood.…”
Section: Epilepsy Currentsmentioning
confidence: 99%
“…Dans la SLA, les essais précliniques chez l'animal utilisant des cellules souches embryonnaires, des CSM ou des précurseurs neuraux dérivés d'IPSC, injectés IV ou directement en intra lésionnel, ont montré des résultats encourageants 1 . Des essais cliniques récents utilisant des injections de CSM en intrathécale ont présenté des résultats encourageants chez les patients atteints de SLA mais nécessitent d'être confirmés sur de plus larges cohortes 18,19 .…”
Section: Quelles Cellules Pour Quelles Applications En Neurologie ?unclassified
“…Plusieurs études expérimentales et/ou essais cliniques ont étudié l'utilisation de différents types de cellules souches pour le traitement de pathologies neurologiques, en particulier celles pour lesquels aucun traitement curatif n'existe comme la maladie d'Alzheimer, la maladie de Parkinson, la maladie de Huntington, la sclérose latérale amyotrophique, et la sclérose en plaques. Mais des études se développent également dans d'autres indications telles que les lésions traumatiques de la moelle épinière ou l'accident ischémique cérébral 1 .…”
Section: Introductionunclassified
“…6,7 Stem cell transplantation offers a promising approach for the treatment of neurological diseases and repair of nerve injuries, and can replace lost neurons in the lesion area, induce an increase in neuroprotective molecules, as well as regulate immune and inflammatory responses. 8,9 Researchers have attempted to use various types of stem cells, such as embryonic stem cells (ESCs), neural stem cells (NSCs), and mesenchymal stem cells (MSCs), to treat neurological disorders, and some of them have been used in clinical trials. 8,10 For example, phase I and II clinical trial results have shown that transplanted stem cells can improve the recovery of patients with early ischemic stroke by reducing neuroinflammation and promoting neurogenesis and angiogenesis, 11 and improve the overall mean functional outcomes of spinal cord injury patients.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Researchers have attempted to use various types of stem cells, such as embryonic stem cells (ESCs), neural stem cells (NSCs), and mesenchymal stem cells (MSCs), to treat neurological disorders, and some of them have been used in clinical trials. 8,10 For example, phase I and II clinical trial results have shown that transplanted stem cells can improve the recovery of patients with early ischemic stroke by reducing neuroinflammation and promoting neurogenesis and angiogenesis, 11 and improve the overall mean functional outcomes of spinal cord injury patients. 12 Although some achievements have been made, it is noteworthy that more clinical trial results have not shown functional improvement, and there are still many problems that need to be solved.…”
Section: Introductionmentioning
confidence: 99%